2011
DOI: 10.1002/kin.20560
|View full text |Cite
|
Sign up to set email alerts
|

Quasiclassical trajectory study of the rotational distribution for the O+NO(v = 0) fundamental vibrational excitation

Abstract: Quasiclassical trajectories have been run to study the fundamental one-quantum vibrational transition formed from collisions of ground-state nitric oxide with atomic oxygen at temperatures of 500, 750, and 1000 K. Two adiabatic potential energy surfaces of different symmetry ( 2 A and 2 A of NO 2 ) have been utilized. The rate constant for the title process is given along with the rotational distributions, and the results shown to corroborate previous atmospheric models that describe the nascent state by a Max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Both the excitation and the relaxation reaction has been studied over a wide temperature range (see ), and the rate constant is known probably within a factor of two. Calculations with this reaction added to the reaction mechanism confirms the assumption of Bowman that the vibrational states of NO are rapidly equilibrated, and modeling predictions are not sensitive to the relaxation rate constant.…”
Section: Resultsmentioning
confidence: 99%
“…Both the excitation and the relaxation reaction has been studied over a wide temperature range (see ), and the rate constant is known probably within a factor of two. Calculations with this reaction added to the reaction mechanism confirms the assumption of Bowman that the vibrational states of NO are rapidly equilibrated, and modeling predictions are not sensitive to the relaxation rate constant.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, early work by Kaplan et al has shown that such a reversibility condition may be applicable to vibrational excitation if the reactants are thermalized. On the other hand, a quasiclassical dynamics study of the excitation process O + NO­( v = 0 → 1) concluded that such a method can be statistically challenging and the microreversibility process applicable only if the translational and rotational thermal conditions are verified both for the reactants and products . Experimental work by Hwang has additionally shown that such an assumption is valid.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of global PESs for the 1 2 A″ state has also been a subject of interest, mostly due to investigations employing reaction dynamics of the NO vibrational relaxation ,, via reactions and , as well as the exchange and recombination reactions . Duff and Sharma have build PESs for both 1 2 A′ and 1 2 A″ states by adding an extra term to existing London–Erying–Polanyi–Sato (LEPS) forms.…”
Section: Introductionmentioning
confidence: 99%